Analisis Morfologi dalam Penggunaan Kosakata Siswa pada Teks Fantasi - Pangestuti, Peni (Program Studi Magister Linguistik Terapan UNJ, 2024)
This research aims to identify the forms of affixation, reduplication, and fusion in the use of vocabulary in fantasy texts of students. This research is a descriptive qualitative research. The data in this research is in the form of affixation, reduplication and fusion. The data source in this research is the fantasy text of seventh grade students of SMP Negeri 2 Babelan. Data collection techniques are observation, interview, documentation, listening, and note taking. The data analysis technique used in this research is the flow model of analysis of the Miles and Hubermen model. The result of the research shows that: (1) The forms of affixation used in the description text of students are prefixes, infixes, suffixes, and confixes. Prefixes consist of ber-, meN-, peN-, di-, ter-, se-, and ke- prefixes. Infixes only contain the infix -em-. Suffixes consist of -i, -an, -nya and -kan. Confixes consist of ke-an, ber-an, pe-an, se-nya, me-kan, and per-an. Affix usage errors occur in the prefixes ber-, meN-, peN-, di-, suffixes -nya, -kan, and the confixes me-i, di-kan, di-i, ter-kan. (2) Forms of reduplication used in the fantasy texts of students, namely root repetition (full repetition, partial repetition, repetition changing sound) and basic repetition with affixes. Reduplication errors occur in whole root repetition and partial repetition.